PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX, KUALITAS AUDITOR DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Yang Terdaftar Di The Indonesian Institute For Corporate Governance Tahun 2010-2014) - Addienda Kamilia Insani, 12.05.52.0189; Indarti, MG Kentris (Students' Journal of Accounting and Banking, 2016)
This research aims to examine and analyze the effect of Corporate Governance Perception Index, quality auditors proxy with auditor independence and auditor reputation, as well as leverage on earnings management. Company size are used as control variables in research. Researchers used a sample of companies listed on the Indonesian Institute for Corporate Governance 2010-2014. Source data used are secondary data obtained from SWA and financial statement data comes from IDX. The sampling method using purposive sampling. About 35 companies sampled in the study. Data analysis method is by using multiple linear regression. The results showed variables CGPI and leverage have significant negative effect on earnings management. Auditor independence and auditor reputation have positive effect but not significant. Size as a control variable can not fix the model, so it does not function as a control variable.Keywords: Corporate Governance Perception Index, Quality Auditor, Auditor Independence, Reputation Auditor, Leverage, Company Size, Earnings Management